2022
DOI: 10.1007/s11864-021-00931-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies for Malignancies of the External Auditory Canal

Abstract: Opinion statementMalignant tumors of the external auditory canal (EAC) are rare tumors in the head and neck. Delayed diagnosis is not uncommon because the symptoms of early tumors are nonspecific. Various surgical and oncological treatment modalities have been reported. Decision-making depends on pathological feature and stage of the lesions, patient’s general condition and preference, and physician’s experience and skill. Radical surgery is widely accepted as the primary treatment of choice. Postoperative rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…Unfortunately, TBSCC of the EAC are often diagnosed late; in the literature, average time from symptom presentation to diagnosis ranges from 12.4 months to 3.9 years [ 47 ]. Consequently, the rate of advanced tumors at diagnosis is high; in our pooled analysis, we found 57.1% of cT3-4 tumors at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, TBSCC of the EAC are often diagnosed late; in the literature, average time from symptom presentation to diagnosis ranges from 12.4 months to 3.9 years [ 47 ]. Consequently, the rate of advanced tumors at diagnosis is high; in our pooled analysis, we found 57.1% of cT3-4 tumors at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The parotid is also susceptible to extension of tumor in the EAC. It has been reported that the incidence of parotid involvement in SCC of the EAC is between 10 and 62% of patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…So, to improve their prognosis, external-beam radiotherapy (EBRT) in conjunction with chemotherapy can be applied. Impressive results by Nagano et al [15] from 21 patients with stage III-IV EAC cancer and Katano et al [16] from 34 patients with stage I-IV EAC cancer suggest that the combination therapy of EBRT and surgery and/or chemotherapy may be the most effective treatment options for advanced EAC cancer. Actually, EBRT with simultaneous chemotherapy is the most acceptable pattern.…”
Section: Determining the Place Of Radiation In The Treatment Of Eac C...mentioning
confidence: 99%
“…The docetaxel + cisplatin + 5FU (DCF) regimen seems the most effective method with high overall survival and reduced loco-regional recurrences. Some studies support the infusion of intra-arterial cisplatin in combination with radiotherapy for locally advanced cases [ 17 ]. Moreover, induction chemotherapy has been shown to convert potentially unresectable tumors to a resectable disease that could produce better outcomes.…”
Section: Improvement Of the Prognosis Of Eac Carcinomasmentioning
confidence: 99%